2023
DOI: 10.1166/jon.2023.1985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Non-Similar Modeling for Thermal Transport Analysis of Mixed Convective Flows of Nanofluids Over Vertically Permeable Surface

Abstract: In the current article, non-similar model is developed for mixed convective boundary layer flow over a permeable vertical surface immersed in nanofluid. The flow is initiated due to the plate stretching in vertical direction and by natural means such as buoyancy. The governing dimensional equations are converted to non-dimensional equations through characteristic dimensions. Furthermore the non-similar modeling is done by choosing ξ (X) as non-similarity variable and η(X, Y) as pseudo-similarity variable. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Tese are particularly useful for analyzing the fow and heat transfer phenomenon scales with changing parameters like Reynolds and Nusselt numbers. Tere are a lot of situations when one needs to introduce nonsimilar transformations [38] to convert this physical system into a nondimensional form. Such situations arise when nonstandard boundary conditions [39][40][41] are introduced in the mathematical description of the fow problems.…”
Section: Similarity Transformationsmentioning
confidence: 99%
“…Tese are particularly useful for analyzing the fow and heat transfer phenomenon scales with changing parameters like Reynolds and Nusselt numbers. Tere are a lot of situations when one needs to introduce nonsimilar transformations [38] to convert this physical system into a nondimensional form. Such situations arise when nonstandard boundary conditions [39][40][41] are introduced in the mathematical description of the fow problems.…”
Section: Similarity Transformationsmentioning
confidence: 99%
“…TiO nanoparticles find applications across a wide spectrum of products and fields, encompassing areas such as nanomedicine, nanobiotechnology, solar panels and electrochemical batteries, production of food, soil rehabilitation, gas detection technology, polymers, paint and parchment industries, hydrogen fuel generation, as well as inks used for printing (Shi et al ., 2013; Akakuru et al ., 2020). In addition, the dynamic features of HNF flow in a porous medium are not being investigated using the LNS technique (Sparrow and Yu, 1971; Razzaq and Farooq, 2021; Hussain et al ., 2023). Numerical solutions for systems of nonlinear-coupled partial differential equations (PDEs) may be obtained by combining the LNS technique with the bvp4c algorithm up to its second truncation level.…”
Section: Introductionmentioning
confidence: 99%
“…This enhanced thermal conductivity has significantly bolstered the efficiency of energy transmission, elevating nanofluids to a prominent position in research endeavors. Hussein [9] delved into the thermal characteristics of laminar nanofluid flow within a tube design. The study revealed an improvement in heat conductivity with increasing nanoparticle fractions.…”
Section: Introductionmentioning
confidence: 99%